MENINGKATKAN PRESTASI BELAJAR MATERI HIDUP DAMAI MELALUI METODE CERAMAH DENGAN BERMAIN KUIS MENGGUNAKAN MEDIA POWERPOINT PADA SISWA KELAS II SD NEGERI PARAKAN 04 BOGOR - Aulia Oktami Putri; Muhammad Rizal (Jurnal Cendekia Ihya, 2023)
In using the method the teacher must adapt to the conditions and atmosphere of the class. The number of children affects the use of the method. In formulating goals, teachers need to formulate them clearly and can be measured. That way it is easy for the teacher to determine which method is chosen to support the achievement of the goals that have been formulated. This classroom action research will discuss efforts to improve learning achievement of peaceful living material through the lecture method by playing quizzes using powerpoint media for grade ii students of SD Negeri Parakan 04 Bogor.